An Early Miocene Lowland on the Northeastern Tibetan Plateau - Tian, Qian; Fang, Xiaomin; Bai, Yan; Chen, Chihao; Hou, Juzhi; Zhang, Tao (Frontiers in Earth Science, 2021)
The northeastern Tibetan Plateau (NE TP) has long been thought to be the last part of the Plateau to be raised, but this assumption has been challenged by recent analyses of fossil leaf energy, which have pointed to the possibility that the present surface altitude of ~3,000 m above sea level (asl) in the Qaidam Basin (QB) was attained during the Oligocene. Here, for the first time, we present a record of glycerol dialkyl glycerol tetraethers (GDGTs) from a well-dated Cenozoic section in the QB. This record appears to demonstrate that the mean annual average paleotemperature of the QB was 28.4±2.9ºC at ~18.0 Ma. This would suggest that the paleoelevation of the QB was only ~1,488 m asl at that time and that a ~1,500 m uplift was attained afterwards, in agreement with the massive shortening of the QB and the rapid drying of inland Asia since the late Miocene.